Nutritional Profile of Commercialized Plant-Based Meat: An Integrative Review with a Systematic Approach - Bernardo Romão; Raquel Braz Assunção Botelho; Maria Luiza Torres; Dayanne da Costa Maynard; Maria Eduarda Machado de Holanda; Vinícius Ruela Pereira Borges; António Raposo; Renata Puppin Zandonadi (Foods, 2023)
Given the high cost of production of animal-based meats and the increase in the number of adepts of meatless diets, the need for plant-based meat substitutes is growing. In this prosperously growing market, there is a lack of knowledge about the nutritional value of these meat substitutes and their ingredients. This study aims to review the nutritional composition and ingredients of meat substitutes commercialized worldwide. An integrative review was performed with a systematic literature search in PubMed, EMBASE, Scopus, Science Direct, Web of Science, and 11 studies were selected to compose the sample of this review. Data on meat substitutes’ nutritional composition and ingredients from different categories were collected and analyzed. The results showed that meat substitutes commonly present lower energy values and higher amounts of carbohydrates and dietary fiber. Protein values varied according to the meat substitute category, with some showing a higher concentration than others, more specifically in substitutes for bovine meat. Higher values were found in the Pieces category and lower in Seafood substitutes. Unlike animal meat, vegan meat has a proportion of carbohydrates higher than protein in most samples, except for chicken substitutes. Meat substitutes presented similar total and saturated fat content compared to their animal-based counterparts. Higher amounts of fat were found in the “Various” category and lower in “Pieces”. Ingredients such as soy, pea, and wheat were the primary protein sources in meat substitutes, and vegetable oils were their primary fat source. Methylcellulose, various gums, and flavorings were the most used food additives. In general, meat substitutes presented high concentrations of sodium, possibly collaborating with an excessive sodium intake, highlighting the need for developing sodium-reduced or sodium-free alternatives. Most of the included samples did not describe the concentration of iron, zinc, and vitamin B12. Further studies are needed to develop meat substitutes with better nutritional composition, fulfilling the need for equivalent substitutes for animal-based meat.